Bidirectional diode-triggered silicon-controlled rectifiers for low-voltage ESD protection - Liu, Wen (2013)
A new bidirectional electrostatic discharge (ESD) protection device is reported in this letter. It consists of a bidirectional silicon-controlled rectifier and diode strings. Such a structure can offer an effective ESD protection solution for low-voltage integrated circuits due to its small design window, small footprint, and high ESD robustness.